A review of recent literature on the impact of parental substance use disorders on children and the provision of effective services. Issue 4 (July 2018) - Straussner, Shulamith L.A.; Fewell, Christine H.
Abstract : Purpose of review: To provide an update of recent studies of the incidence and impact of parental substance use disorders (SUDs) on children, and to identify effective treatment programs to assist parents with SUDs and their children. Recent findings: Children of parents with alcohol and drug use disorders (COPADs) suffer from physical, mental and behavioral problems at higher rates than other children and are more likely to develop their own SUDs in adolescence. Parenting styles and familial dysfunction contribute to the intergenerational transmission of SUDs. Studies of the negative effects of parental SUDs on children identified the effects of inconsistent, disengaged or harsh parenting practices on mother–child bonding. Exposure to violence and father's hostility contribute to children's externalizing and internalizing behaviors. Family- based intervention programs, as well as programs for mothers with SUDs and their young children, have shown positive results. For high-risk families with multiple needs, the ongoing support of multidisciplinary services is required. Summary: Parental SUDs have a profound impact on their children, including intergenerational transmission of SUDs. A variety of interventive programs are being studied in order to devise effective programs to assist these children.